Neuropsychological Profile of College Students Who Engage in Binge Drinking - Kang, Jae-Gu; Kim, Myung-Sun (Frontiers in Psychology, 2022)
This study investigated the neuropsychological profile of college students who engage in binge drinking (BD) using comprehensive neuropsychological tests evaluating verbal/nonverbal memory, executive functions, and attention. Groups were determined based on scores on the Korean version of the Alcohol Use Disorder Identification Test (AUDIT-K) and Alcohol Use Questionnaire (AUQ). There were 79 and 81 participants in the BD and non-BD groups, respectively. We administered the Korean version of the California Verbal Learning Test (K-CVLT) and Rey-Osterrieth Complex Figure Test (RCFT) to evaluate verbal and nonverbal memory, respectively, and measured executive functions using the Wisconsin Card Sorting Test (WCST), Trail-Making Test, Controlled Oral Word Association Test and Stroop Color-Word Test. We administered the d2 test to evaluate attention. Neuropsychological performance was analyzed by multivariate analysis of variance. The BD group showed significantly poorer performance in the long-term free recall condition of the K-CVLT and delayed recall condition of the RCFT and completed significantly fewer categories on the WCST than the non-BD group. In addition, there were significant negative associations among the AUDIT-K total score, AUQ binge score, and long-term free recall score of the K-CVLT. There were significant negative associations between the total AUDIT-K score and delayed recall RCFT score, and between the total AUDIT-K total score and numbers of completed categories on the WCST. These results indicate that college students who participate in BD have difficulties with verbal/nonverbal memory and executive functions, and further suggest that excessive alcohol use could have detrimental effects on the hippocampal-prefrontal circuit even with a relatively short period of alcohol use.